Multicenter Evaluation of the Bruker MALDI Biotyper CA System for the Identification of Clinically Important Bacteria and Yeasts. Issue 6 (13th May 2017) - Wilson, Deborah A.; Young, Stephen; Timm, Karen; Novak-Weekley, Susan; Marlowe, Elizabeth M.; Madisen, Neil; Lillie, Jennifer L.; Ledeboer, Nathan A.; Smith, Rebecca; Hyke, Josh; Griego-Fullbright, Christen; Jim, Patricia; et al.
Abstract : Objectives: A report on the multicenter evaluation of the Bruker MALDI Biotyper CA System (MBT-CA; Bruker Daltonics, Billerica, MA) for the identification of clinically important bacteria and yeasts. Methods: In total, 4, 399 isolates of medically important bacteria and yeasts were assessed in the MBT-CA. These included 2, 262 aerobic gram-positive (AGP) bacteria, 792 aerobic gram-negative (AGN) bacteria 530 anaerobic (AnA) bacteria, and 815 yeasts (YSTs). Three processing methods were assesed. Results: Overall, 98.4% (4, 329/4, 399) of all bacterial and yeast isolates were correctly identified to the genus and species/species complex level, and 95.7% of isolates were identified with a high degree of confidence. The percentage correctly identified and the percentage identified correctly with a high level of confidence, respectively, were as follows: AGP bacteria (98.6%/96.5%), AGN bacteria (98.5%/96.8%), AnA bacteria (98.5%/97.4%), and YSTs (97.8%/87.6%). The extended direct transfer method was only minimally superior to the direct transfer method for bacteria (89.9% vs 86.8%, respectively) but significantly superior for yeast isolates (74.0% vs 48.9%, respectively). Conclusions: The Bruker MALDI Biotyper CA System accurately identifies most clinically important bacteria and yeasts and has optional processing methods to improve isolate characterization.